DAKWAH DAN DIMENSI AKULTURASI BUDAYA - Khoriyah, Nunung (Fakultas Dakwah IAIN Purwokerto, 2011)
Since its early spread, Islamic dakwahÂ in Indonesia has shown its strong accommodation to local cultures thatthe arrival of Islam was not considered as a threat, but a companion which plays an important role in the cultural transformation. It shows thatthe charaderof Islam in Indonesia is accommodative to social tradition and cultures of the local people. This accommodative model was one of the charaderistics of Indian mubaligh, which is then followed by Walisongoin their dakwahin Java. The dialogue process belween Islam and social tradition was adualized in the mechanism of cultural process to face the local cultures. The combination between Islam and social cultures is a local interpretation to not make Islam too far from the real condition ofthe local people. Islam was not viewed as itwas in Arab, but there should be a dialogue between Islam and the local cultures.